Quantum‐dot color conversion towards white‐balanced healthy displays: Theoretical and simulation study. Issue 11 (14th August 2022) - Xu, Sheng; Lin, Xinyu; Zhang, Xiang; Chen, Enguo; Ye, Yun; Guo, Tailiang; Yan, Qun Frank
Abstract: Quantum‐dot (QD) color conversion (QDCC) has the inherent advantages of high color purity and adjustable spectral peak, and spectral symmetry, which is favorable to healthy displays. In this paper, a theoretical design for QDCC white balance in healthy displays is proposed to achieve both high light conversion efficiency ( LCE ) and low blue light intensity ( BLI ). Based on the defined logical channels for QDCC model and the optimal criterion of the QD's dosage factor ( DoF ), the key design parameters of the red and green QDCC sub‐pixels are first obtained, including the QD concentration and the color conversion layer thickness. Then, according to the requirements of three‐primary‐color flux for white‐balanced display, the luminous area of three‐primary‐color sub‐pixels can be adjusted to achieve the white balance of the healthy display. Finally, by combining the above theoretical analysis and design approach, a theoretical formula is recommended for white‐balanced healthy displays with high luminous efficiency and low BLI . The white balance method is verified by theoretical derivation and optical simulation. Results show that the method can not only guide the structural design of the QDCC from the theoretical level but also ensure high LCE and low BLI for three‐primary‐color sub‐pixels. The target white balance can be well achieved by adjusting the area ratio of three‐primary‐color sub‐pixels to 3.94:5.06:1, and the color coordinates and the color temperature are (0.313, 0.3206) and 6552 K, respectively. This study provides a useful exploration of QDCC white balance design for next‐generation healthy displays with high conversion efficiency and low BLI . Abstract : A theoretical model for quantum‐dot color conversion (QDCC) is established by the definition of two logical channels. Based on this, a design method for QDCC white balance in healthy displays is proposed to achieve both high light conversion efficiency and low blue light intensity. This provides indispensable theoretical guiding and feasibility basis for QD healthy displays.